Centering Female Protagonists: explorations of Ama Ata Aidoo’s influence in Lola Shoneyin’s The Secret Lives of Baba Segi’s Wives and Guillermina Mekuy’s Tres almas para un corazón - Lomotey, Benedicta A.; Boampong , Joanna (Africanías. Revista de Literaturas, 2024)
By all accounts, Ama Ata Aidoo can be heralded, together with writers like Flora Nwapa and Mariama Ba, as a trailblazer in African literature and African feminist thinking. A staunch defender of African value systems, her works centre female protagonists and explore the complexities involved in exercising agency, seeking self-fulfilment, coming into a full realization of themselves or their human condition. A key aspect of her work is how it resonates with younger generations of female African writers after her. In an Interview with Madeleine Thien in 2013, Tsitsi Dangarembga credits Aidoo’s experience as a black woman in Germany as the inspiration for Tambudzai, the protagonist of her Nervous Conditions (1988). Similarly, Chimamanda Ngozi Adichie affirms in The Africa Report (January 20, 2011) that “Her storytelling nurtured mine. Her worldview enlarged and validated mine” (np). Our aim, in this paper, is to examine the extent of Ama Ata Aidoo’s influence on Lola Shoneyin and Guillermina Mekuy, two writers of the Anglophone and Hispanophone literary traditions respectively. Drawing on the theoretical frameworks of postcolonial African feminism, intertextuality (Kristeva) and dialogism (Bakhtin) we examine ways by which Lola Shoneyin’s The Secret Lives of Baba Segi’s Wives (2010) and Guillermina Mekuy’s Tres almas para un corazón (2011) [Three Souls for One Heart] engage Ama Ata Aidoo’s Changes: A Love Story (1991). Like Esi in Aidoo’s novel, Bolanle in Shoneyin’s and Aysha in Mekuy’s are formally educated female protagonists who opt for polygamous marriages. While these protagonists raise questions regarding women’s exercise of freedom and agency, and their quest for self-fulfilment, do their works communicate similarly? How do the latter novels, in their approach and engagement with the polemic topic of polygamy, echo, revise, or build on Ama Ata Aidoo’s legacy? Do they reimagine and posit new perspectives?